Modifikasi Rumah Kutai Knockdown Sebagai Solusi Perumahan Daerah Rawa - Anna Rulia; Anton Esfianto (LP2M ISBI Bandung, 2018)
AbstractIn order to fulfil the needs of housing in Indonesia, a construction in the swampy area is a significant challenge due to its wet condition. Housing offered by the developers commonly appears as a permanent construction which closes the waterway and enlarges the risk of flooding. The permanent construction also takes more time to build in comparison with a traditional housing. Meanwhile, people prefer a permanent construction and modern architecture to a traditional style such as Kutai housing style. This research aims to explore the design of Kutai housing style with the knockdown system as an alternative solution to fulfil the needs of housing in the swampy area. By using the five steps architectural design methods, this design is considered to be more effective due to the shorter time used as well as its effectiveness to prevent flooding. Moreover, the simple yet beautiful design of Kutai housing style gives a strong sense of place and can be seen as a way to preserve a traditional architecture that can also be sold outside the island.Keywords: swamp, Kutai, housing, knockdown designAbstrak Untuk memenuhi kekurangan perumahan di Indonesia, konstruksi pada daerah rawa merupakan tantangan tersendiri karena karakternya yang khas. Perumahan yang dibangun oleh developer umumnya merupakan konstruksi permanen yang pengerjaannya lebih lambat dibandingkan dengan rumah tradisional serta menutup jalur air rawa sehingga dapat mengakibatkan banjir. Selain itu, masyarakat pun saat ini lebih memilih desain permanen ketimbang arsitektur tradisional seperti rumah Kutai. Penelitian ini bertujuan untuk mendiskusikan rancangan rumah Kutai sebagai solusi alternatif dengan sistem knockdown, sebagai pemenuhan kekurangan perumahan di daerah rawa, seperti Kalimantan. Dengan metode perancangan lima langkah dalam arsitektur, desain ini diharapkan dapat lebih efektif karena singkatnya waktu pengerjaan dan efektivitasnya dalam mencegah banjir. Desain rumah Kutai yang sederhana tapi estetis ini dapat memberi daya tarik kelokalan yang khas, dapat menjaga kelestarian arsitektur tradisional, juga dapat memberi dampak ekonomi bagi masyarakat setempat.Kata kunci: lahan rawa, Kutai, rumah, model knockdown